CONTRIBUTION TO KNOWLEDGE OF THE FAUNA OF CYNIPID GALL WASPS (HYMENOPTERA: CYNIPIDAE) OF MT. JASTREBAC (SERBIA) (Acta Entomologica Serbica, 2014)
Thirty-four species in all were recorded in investigation of the fauna of cynipid gall wasps on Mt. Jastrebac. That number includes 30 species from seven genera (Andricus, 20 species; Cynips, four; Neuroterus, two; Aphelonyx, one; Biorhiza, one; Dryocosmus, one; and Pseudoneuroterus, one) of the tribe Cynipini; and four species from one genus (Diplolepis) of the tribe Diplolepidini. The species Andricus conificus (Hartwig 1843) and Cynips cornifex Hartwig 1843 are here reported for the first time for the fauna of cynipid gall wasps of Serbia. For the recorded species of cynipid gall wasps, the localities, dates, and host plants at Mt. Jastrebac are given in the paper.